Project Scope Management: A Strategy Oriented to the Requirements Engineering - Lampa, Igor Luiz [UNESP]; Contessoto, Allan de Godoi [UNESP]; Amorim, Anderson Rici [UNESP]; Donega Zafalon, Geraldo Francisco [UNESP]; Valencio, Carlos Roberto [UNESP]; Gratao de Souza, Rogeria Cristiane [UNESP]; Hammoudi, S.; Smialek, M.; Camp, O.; Filipe, J. (Scitepress, 2017)
Scope management is an area of project management defined by PMBoK, which has processes to register and control everything that belongs to the project boundaries. Although the relevance of this area to the success of projects, its application is still a challenge, which is potentialized by the lack of computational tools to support project management that integrate the scope management totality. In addition, the lack of understanding of project requirements is another factor that hinders the execution of this area, because often the stakeholders do not have full knowledge of their needs at the beginning of the project, resulting in changes throughout the project lifecycle, which increases the costs and deadlines. In this sense, the objective of this work is to propose the integration of the scope management with the requirements engineering, in order to better identify the requirements of a project and to understand what needs to be done, contributing to the success of projects. For the evaluation of the results obtained, a requirements engineering module was developed and integrated with a previously developed computational tool for project management and it aims to assist the application of the project management following the guidelines and good practices proposed on PMBoK.
Keywords: Project Management; Scope Management; Requirements Engineering